Review Article on Shatakriyakala :A Way to Know & Treat Diseases. - Sonawane, Gupteshwar (International Research Journal of Ayurveda & Yoga, 2023)
The term Kriya kala refers to the recognition of the stage of a disease’s Progress. This concept is mostly compared with disease Pathogenesis. Kriyakala means the time of treatment or interception in the process of disease Manifestation. Acharya Susrutha has narrated detail idea of Shatkriyakala in 21st chapter of Sutrasthana. Shatkriyakala include six stages viz Sanchaya, Prakopa, Prasara, Sthansamshraya, Vyaktavastha and Bhedavastha. That means 6 (the number Six). Kriya means Action or treatment. Kala means Time or period. So Shatkriyakala Means ‘Appropriate time Periods to take action/treatment. The Prayojana of Ayurveda is of two types, Maintenance of health a healthy Person, by adopting the Ritucharya, Dincharya and Sadvritta and curing of a Disease of diseased Person, by adopting therapeutic measures. Before Studying the Pathological conditions of the body, a Physician has to first study the occult function and structures of the body on the basic of dosa, dushya And Srotas. At that time kriya Kala helps the doctor to adopt line of treatment by Seeing the vitiated dosha Condition by his intellect and knowledge.